Hybrid sterility genes in mice (Mus musculus): a peculiar case of PRDM9 incompatibility - Forejt, Jiri; Jansa, Petr; Parvanov, Emil (Trends in genetics, 2021)
Hybrid sterility is a critical step in the evolution of reproductive barriers between diverging taxa during the process of speciation. Recent studies of young subspecies of the house mouse revealed a multigenic nature and frequent polymorphism of hybrid sterility genes as well as the recurrent engagement of the meiosis-specific gene PR domain-containing 9 (Prdm9) and X-linked loci. Prdm9-controlled hybrid sterility is essentially chromosomal in nature, conditioned by the sequence divergence between subspecies. Depending on the Prdm9 interallelic interactions and the X-linked Hstx2 locus, the same homologs either regularly recombine and synapse, or show impaired DNA DSB repair, asynapsis, and early meiotic arrest. Thus, Prdm9-dependent hybrid sterility points to incompatibilities affecting meiotic recombination as a possible mechanism of reproductive isolation between (sub)species.
Keywords: meiotic sex chromosome inactivation; zvířata; meiotic recombination; Meiosis; chromosome-autonomous asynapsis; mužská infertilita; myši; Mice; meióza; reprodukční izolace; Histone-Lysine N-Methyltransferase; Reproductive Isolation; Infertility, Male; hybrid sterility; histonlysin-N-methyltransferasa; Animals; Homologous Recombination; Prdm9; homologní rekombinace